O papel de Deus na cura segundo Viktor Emil Frankl - Machado, Ana Enésia Sampaio (2010)
This paper addresses the relationship between God and the cure of meaningless neuroses. From the works of Viktor Frankl, the Viennese psychiatrist and psychologist, this paper describes what are these neuroses, called noogenics, neuroses that have their origin in the dimension of the human existence. The concept of noogenic neurosis goes beyond a psychophysical condition, therefore, to the author, the human being is essentially spiritual. This spiritual core, around which are grouped the psychic and physical, is responsible for the moral conscience, love and art. As the modern man deviates himself away from his religion, he has increased the existential emptiness, because he can not find a reason for his actions, which can lead to a lack of meaning, characteristic of noogenic neurosis. Thus, the man would get ill in his spirituality. For this type of illness, Frankl has created the Logotherapy. A specific type of such spiritual disease is the mass neurosis, which is the highlight of this research. For the author, God, who is the ultimate meaning of human existence, dialogues with the man when he talks to his own moral conscience, which is transcendent. Using the concepts of God and man given by the author, this research addresses the relationship between human being and the transcendence and how it would, through this relationship, and a subsequent meeting with the meaning, the cure of the mentioned neuroses